Optimizing Layout Structure in the ASOS Application Using the GeM Framework - Wardhani, Nabila Kusuma (Journal of Pedagogy and Education Science, 2024)
The study aims to identify key elements such as icons, text, and paragraphs within the ASOS application. The research seeks to provide insights into the application's design, emphasizing simplicity that appeals more to younger users compared to adults. The study employs a qualitative descriptive research method to analyze the data, which consists of screenshots from the ASOS application taken on a mobile phone. Data collection focuses on various screens, including the home screen, categories screen, Ramadhan edit screen, brand screen, my bag screen, and add address screen. The analysis reveals that the application contains numerous hyperlinks facilitating the selection and purchase of goods. From the examined screens, the author identifies 207 base units, which are further classified into 51 base layouts.